(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
According to WHO estimation the global occurrence of uterine prolapse is increasing and is assumed to be two to twenty percent. In Ayureda Doshas involved in Prasramsini Yonivyapa is Pitta Pradhan Vata Dosha. So, for the Samprapti Vighatana of Prasramsini Yonivyapada treatment should emphasize mainly on Pitta and Vata Shamana. Acharaya Sushruta has described Prasramsini Yonivyapada in Pittaja Yonivyapada which can be correlated with and first and second degree uterine prolapse. This condition is usually encountered in perimenopausal or postmenopausal period although young age group with distress during labor is not an exemption. A 42 years old female presented with first degree uterine prolapse was treated with Yoni Dhadhyakara Lepa (Madanphala, Madhuyasti, Karpura) followed by Yoniprakshalana with Triphala Kwatha. This treatment was continued for seven days twice daily for three consecutive months with positive outcome and good symptomatic relief in the patient.